Association of PTSD With Longitudinal COVID-19 Burden in a Mixed-Serostatus Cohort of Men and Women: Weathering the Storm. (15th August 2022) - Jones, Deborah L.; Zhang, Yuehan; Rodriguez, Violeta J.; Haberlen, Sabina; Ramirez, Catalina; Adimora, Adaora A.; Merenstein, Daniel; Aouizerat, Bradley; Sharma, Anjali; Wilson, Tracey; Mimiaga, Matthew J.; Sheth, Anandi N.; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: This study of people with HIV (PWH) and those without HIV conducted during the COVID-19 pandemic in the United States in 2020 examines the impact of posttraumatic stress disorder (PTSD) on COVID-19 burden, defined as pandemic-related disruptions. Methods: Data consisted of survey responses on PTSD among participants (N = 2434) enrolled in the Multicenter AIDS Cohort Study (MACS) and the Women's Interagency HIV (WIHS) cohorts. Unadjusted and adjusted regression models were used to examine the association of PTSD with COVID-19 burden (overall and domain-specific burdens). Quasi-Poisson regression models were used to assess associations with the COVID-19 burden score and 2 domain-specific burdens: (1) changes in resources and (2) interruptions in health care. Analyses was adjusted for age, race/ethnicity, HIV serostatus, current smoking status, number of comorbidities, education, and study regions. Results: Study participants were a median age of 58 (interquartile range, 52–65) years. In both bivariate and multivariable models, PTSD severity was associated with greater overall COVID-19 burden. PTSD severity was associated with the number of resource changes and number of interruptions in medical care. These findings were also consistent across cohorts (MACS/WIHS) and across HIV serostatus, suggesting a greater risk for COVID-19 burden with greater PTSD severity, which remained significant after controlling for covariates. Conclusions: This study builds on emerging literature demonstrating the impact of mental health on the burden and disruption associated with the COVID-19 pandemic, providing context specific to PWH. The ongoing pandemic requires structural and social interventions to decrease disruption to resources and health resource needs among these vulnerable populations.